ISSUES IN PRESERVING NATIONAL IDENTITY IN THE TRANSLATION PROCESS (Scientific journal of the Fergana State University, 2026)
This article provides a scientific and theoretical analysis of the key translation principles that ensure the accurate conveyance of nationally specific words and the full reflection of the author’s individual style. The study examines in detail the challenges encountered in translating national-cultural units, the identification of their equivalents, the preservation of national color, and the clear communication of the text to the reader. Within the scope of the research, Mirzakalon Ismoiliy’s “So‘na” was selected as the object of translation, and practical examples are provided concerning the transfer of national realities, lexical units, figurative expressions, and author-specific stylistic devices into another language. Additionally, the effectiveness of translation methods such as adequacy, equivalence, adaptation, and explanatory translation is evaluated, and conclusions are drawn regarding the most optimal ways to convey national characteristics accurately.